A comparison of the Effect of Quadriceps Taping versus Patellar Taping on Balance and Functional Performance in Patients with Knee Osteoarthritis - Haghighi, Farzaneh Moslemi; Mahbobeh, Samani; Ebrahimian, Maryam; Zare, Mahsa; Bostanian, Mohammad Reza (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Backgrounds Osteoarthritis (OA) is primarily a disease of cartilage destruction. Knee OA is the most common type of arthritis which can be treated with kinesio taping (KT).Purpose The current study was aimed to compare the effect of quadriceps muscle taping vs. patellar taping on balance and functional performance in patients with knee OA.Patients and Methods 40 patients with knee OA aged from 40 to 65 years entered this interventional study. Eligible participants were randomly divided into 2 groups, the Quadriceps taping group, and patellar taping group. The balance was measured using the modified star excursion balance test (SEBT), functional reach test (FRT), and Berg balance scale test (BBST). Also, functional activity was evaluated using the step test. All variables measured before, immediately after and 24 hr after the intervention in both groups.Results Within-group comparison in both groups showed that KT therapy improved modified SEBT, FRT and step test scores immediately after and 24 h after the intervention compared to baseline, and the difference was more significant 24 h after the intervention compared to immediately after the intervention. However, BBS score was not different in assessed times compared to baseline in both groups. The results of between-group analyses of variables showed no significant differences between the two groups in assessed times. Besides, repeated measure ANOVA showed that time significantly influenced modified SEBT, FRT, and step test. However, there was no group effect on assessed variables.Conclusion Both quadriceps and patellar taping positively influenced balance and functional level of the patients with knee OA. Also, there is no superiority between these 2 methods.
Keywords: Osteoarthrose; function; balance